Striatal Signaling in L-DOPA-Induced Dyskinesia: Common Mechanisms with Drug Abuse and Long Term Memory Involving D1 Dopamine Receptor Stimulation - Murer, Mario G.; Moratalla, Rosario (Frontiers in Neuroanatomy, 2011)
Parkinson’s disease is a common neurodegenerative disorder caused by the degeneration of midbrain substantia nigra dopaminergic neurons that project to the striatum. Despite extensive investigation aimed at finding new therapeutic approaches, the dopamine precursor molecule, 3,4-dihydroxyphenyl-L-alanine (L-DOPA), remains the most effective and commonly used treatment. However, chronic treatment and disease progression lead to changes in the brain’s response to L-DOPA, resulting in decreased therapeutic effect and the appearance of dyskinesias. L-DOPA-induced dyskinesia (LID) interferes significantly with normal motor activity and persists unless L-DOPA dosages are reduced to below therapeutic levels. Thus, controlling LID is one of the major challenges in Parkinson’s disease therapy. LID is the result of intermittent stimulation of supersensitive D1 dopamine receptors located in the very severely denervated striatal neurons. Through increased coupling to Gαolf, resulting in greater stimulation of adenylyl-cyclase, D1 receptors phosphorylate DARPP-32 and other protein kinase A targets. Moreover, D1 receptor stimulation activates ERK and triggers a signaling pathway involving mTOR and modifications of histones that results in changes in translation, chromatin modification and gene transcription. In turn, sensitization of D1 receptor signaling causes a widespread increase in the metabolic response to D1 agonists and changes in the activity of basal ganglia neurons that correlate with the severity of LID. Importantly, different studies suggest that dyskinesias may share mechanisms with drug abuse and long term memory involving D1 receptor activation. Here we review evidence implicating D1 receptor signaling in the genesis of LID, analyze mechanisms that may translate enhanced D1 signaling into dyskinetic movements, and discuss the possibility that the mechanisms underlying LID are not unique to the Parkinson’s disease brain.